Lettere alle "tre amiche" - Slataper, Scipio (Alpe Adria e dintorni, itinerari mediterranei, 2022)
This volume presents the letters (approximately 600) that Scipio Slataper wrote between late 1909 and December 1915 to his "three friends" from Trieste, Anna Pulitzer, Gigetta (Luisa) Carniel, and Elody Oblath. These letters bring to light complex existential and intellectual storylines: of friendship, love, and pain, of the search of the purpose of life, cultural commitment, and artistic creation.